Exclusion clause vs non-refoulement principle in relation to mercenaries: Wagner group case - Bidnenko, Oksana (Riga Graduate School of Law, 2024)
When dealing with refugee cases related to individuals involved in military conflicts, it is a challenge to identify the eligibility under the 1951 Convention, especially when the applicant is a member of the notorious mercenary group. This research is focused on the interaction between the interaction of exclusion clause and non-refoulement principle when an applicant is not eligible for refuge in the receiving state. Additionally, this research tends to find out the status of Wagner Group, the case study related to which is performed in the last chapter since mercenarism is not allowed in the Russian Federation.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; mercenarism; international refugee law